THE EFFECT OF THEME-BASED INSRTUCTION COMPARED TO COMPETENCE-BASED LANGUAGE TEACHING TO TEACH READING COMPREHENSION TO STUDENTS WITH IDGH AND LOW INTEREST - Rosyita, Ulya; Faridi, Abdurrachman (English Education Journal, 2017)
This study is an experimental research with a factorial design which aimed to find out the effect of Theme-Based Instruction compared to Competence-Based Language Teaching in teaching reading comprehension to students with high and low interest. The samples of the study were tenth graders of MA Mathali'ul Falah Kajen, Pati in the academic year of 2016/2017. There were two classes, 30 students of XA as experimental class and 30 students of XE as control class. Theme-Based Instruction was used for experimental class, while Competence-Based Language teaching was used in control class. the data of this study were the score of reading comprehension test and interest questionnaire. The result of pretest and posttest were analysed by using T-test and ANOVA The result of this study showed that Theme-Based Instruction and Competence-Based Language Teaching to teach reading comprehension to high and low interest students. Theme -Based Instruction was more effective than Competence-Based Language teaching. There was no interaction among Theme-Based instruction, Competence-Based Language Teaching, reading comprehension and students' interest.